Changes in Platelet Function, Ultrastructure and Plasma Membrane-Associated Proteins (Actin and Tubulin) in Thrombocythemia - Podolsak, B.; Wenzel, E.; Morgenstern, E.; Meiser, R.J. (Thrombosis and Haemostasis, 1979)
Five patients with thrombocythemia (two primary hemorrhagic cases and three symptomatic cases, one with generalised amyloidosis and two with splenectomies after hemoblastosis or hepatosplenomegaly) showed the following pathological platelet functions: platelet count, 8 × 105 - 1.4 × 106/μ1; bleeding time 4 min, 50 sec. - 20 min; adhesiveness (Hellem II) 1.5 - 27%; significantly decreased aggregation with collagen and ADP and decreased platelet spreading capacity.In two patients, clot-retraction was less than normal. The distribution of platelet volumes was normal in all cases. Electron microscopic studies on platelets from these patients showed an increase in microtubular structures and a decrease in electron dense hyaloplasma.Analyses of the platelet membrane proteins from each patients, by SDS-PAGE and staining showed a band at ca. 50,000 daltons (probably tubulin) which was stronger, while in only three cases there was a significant decrease in membrane-associated actin, as compared to normal platelet membranes. In the other patients, the decrease was smaller. In two patients, there was a discrete decrease in the bands corresponding to heavy myosin chains. No essential changes were found in membrane glycoproteins. The changes in the relation between the different cytosoeletal elements could partially explain the impaired platelet function in thrombocythemia.